Hydrodynamic analysis of an axial impeller in a non‐Newtonian fluid through particle image velocimetry. Issue 6 (19th February 2020) - Fernandes del Pozo, David; Liné, Alain; Van Geem, Kevin M.; Le Men, Claude; Nopens, Ingmar
Abstract: The rheology of non‐Newtonian fluids in agitated vessels is complex making equipment sizing more an art than a science. To increase our understanding and to resolve the data gap for computational fluid dynamics validation, we present a detailed particle image velocimetry study of the hydrodynamics of Carbopol encountered in a 70 L mechanically mixed (A310) tank at three different rotational speeds (100, 250, 500 rpm). Bulk flow visualizations show that the flow field below the impeller is highly influenced by the rheological behavior of the fluid. Moreover, an analysis of the shear rate and viscosity revealed important spatial heterogeneities. An estimation of the Reynolds number classified the rotational speeds as the onset of the transitional regime (100), in the transitional regime (250) and turbulent conditions (500 rpm). This data set consists of local mean and fluctuating velocities at different locations below the impeller, which are available for validation and further study.